Quantifying Environment in NU Online Media: Corpus-Based Ecolinguistic Discourse Analysis Perspective - Mukminin, Muhamad Saiful (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2025)
This study aims to identify environmental terms, categorize environmental discourse, and trace the ecological ideologies reflected in NU Online articles. The study employs a mixed-methods approach, combining qualitative and quantitative analyses, using discourse analysis and ecolinguistic frameworks. Data analysis uses an interactive model, supported by theories of word frequency, discourse practices, and ecological ideology. The findings show that NU Online consistently uses environmental terminology that reflects attention to ecological, ethical, and natural resource aspects. Discourse analysis reveals three main categories: conservation discourse, environmental crisis discourse, and eco-Islam discourse. The ecological ideology analysis indicates the presence of both destructive and beneficial discourse, highlighting environmentally damaging practices and promoting conservation and sustainability. Penelitian ini bertujuan mengidentifikasi istilah lingkungan, mengkategorikan wacana lingkungan, dan menelusuri ideologi ekologis yang tercermin dalam artikel NU Online. Studi ini menggunakan metode campuran, dengan pendekatan analisis wacana dan ekolinguistik. Data penelitian berupa 20 artikel NU Online bertema lingkungan yang diperoleh melalui pencarian kata kunci ‘lingkungan’. Analisis data menggunakan model interaktif, didukung dengan teori frekuensi kata, praktik wacana, dan ideologi ekologi. Hasil penelitian menunjukkan bahwa NU Online konsisten menggunakan istilah lingkungan yang mencerminkan perhatian pada aspek ekologi, etika, dan sumber daya alam. Temuan analisis wacana mengungkap tiga kategori utama, yakni wacana konservasi, wacana krisis lingkungan, dan wacana eco-Islam. Analisis ideologi ekologis menunjukkan adanya wacana destruktif yang menyoroti praktik merusak alam serta wacana bermanfaat yang mendorong konservasi dan keberlanjutan.